Prediction of winning amateur boxers using pretournament reaction times - Darby, D.; Moriarity, J.; Pietrzak, R.; Kutcher, J.; Mcaward, K.; Mccrory, P. (The Journal of Sports Medicine and Physical Fitness, 2014)
AIM: Boxing requires agility and manual dexterity, which is associated with fast reflexes and reaction time. This study evaluated the relation between reaction times on cognitive tasks and competition outcomes in boxers. METHODS: The design was a prospective cohort study. Participants were collegiate amateur boxers who won at least one bout in a single elimination tournament. Optimal pre-participation performance using a computerized cognitive assessment tool (CCAT, Axon Sports) and no significant deterioration in cognitive performance within 24 hours post-bout was required to compete in future bouts. Winners were assumed to be motivated to perform optimally on testing. Performance on speed and accuracy measures were compared in winning and non-winning boxers. Pre-competition minutes of sparring and tournament seedings were recorded. RESULTS: There were 96 eligible boxers who won at least one of 160 bouts. The mean age was 21.3 (SD 1.9) years (range 18.5-29.7). A significant improvement in mean reaction times as a function of advancement in the boxing tournament was observed. The 18 winning boxers who advanced to the finals had significantly faster mean reaction times at the baseline assessment before the competition began (speed composite z-score F(1,94)=4.14, P<0.05, effect size 0.54). Winners also had more sparring experience (Mann-Whitney U=302.5, P<0.001) and higher pre-competition rankings (Mann-Whitney U=288.5, P<0.001). CONCLUSION: In highly motivated amateur boxers, finalists performed significantly faster than those who failed to reach the finals on measures of pre-competition reaction time. These findings suggest that winners of boxing tournaments might be predicted using pre-competition measures of processing speed.